The Dow Jones Industrial Average as a Moderator in the Relationship Between Macroeconomic Variables and the JCI - Dwijaya, I Kadek Bellyoni; Azis R, Abdul (Journal of Trends Economics and Accounting Research, 2025)
The purpose of this study is to determine and analyze the effect of macroeconomic variables including Money Supply, BI Rate, Inflation on the Composite Stock Price Index moderated by the Dow Jones Industrial Average Index. Using monthly data for the period 2013 – 2022 as many as 120 observations through a quantitative approach with the Fit model test analysis technique using the Smart-PLS application. The findings show that the Money Supply variable has a negative and insignificant effect, the BI Rate variable has an insignificant effect, Inflation and the Dow Jones Industrial Average have a positive and significant effect on the Composite Stock Price Index. The Dow Jones Industrial Average Index is able to moderate all macroeconomic variables on the Composite Stock Price Index on the Indonesia Stock Exchange. The strength of the United States stock market has a significant impact on the stock prices of developing countries, one of which is Indonesia, meaning that Indonesia's economic conditions are still dependent on developed countries, namely the United States in the long-term period. The reliance on global markets suggests that Indonesian policymakers and investors must carefully track international market trends, especially in the United States, when developing strategies and making investment decisions. The reliance on global markets suggests that Indonesian policymakers and investors must carefully track international market trends, especially in the United States, when developing strategies and making investment decisions.